Design and characterization of a novel diamond resonator. Issue 7 (July 2014) - Maricar, Mohamed Ismaeel; Glover, James; Evans, Gwynne; Ata‐ul‐Khalid; Cumming, David; Oxley, Chris
ABSTRACT In this article, the resonant frequency and quality factor of a novel coplanar waveguide (cpw) diamond‐shaped resonator were analyzed using advanced design system‐2009 momentum model software. The diamond resonator was compared with the cpw radial stub resonator on gallium arsenide (GaAs); the work indicated that the diamond resonator had a smaller physical size and higher quality factor (Q) at millimetric wave frequencies. Experimentally measured diamond cpw resonators fabricated on GaAs were in good agreement with the simulated results. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1691–1693, 2014